Membaca Masa Depan Pendidikan Islam New Normal Di Sekolah MIS YPII Tanjung Pura - Maulida; Fatimah Ahmad; Ima Sari Ramadhani; Muhammad Khalidin (Fusion: Jurnal Pengabdian kepada Masyarakat, 2022)
This paper discusses the relationship between islamic education and various elements of life. The link nbetween the theoretical side of Islmic education and the practical side of Islamic education also reaches here. In terms of study, the theoretical dimensions with the application of Islamic education can be discussed seprately. But in practice they cannot be sparated from oe another. In principle, the issue of Islamic education cannot be separated from other issues. Islamic education is related to vrious elements of life, especially humans. This type of qualitative research uses a field study approach by observasing research locations. Data collection methods through observation, interviews and dokumentation. Data analysis techniques by way of triangulation of data and sources. The result of this study are that learning is quite good by providing direct examples for students. Another skill possessed madrasah ibtidaiyah is the ability to make short speeches related to the application of Islamic teachings in life. This shows that educators are able to develop the talens of students which of course are in accordance with thw demand of educators for the potential of students to hone the future of Islamic education